Numerical simulation of the effects of secondary roughness in the form of extension to arrays of terraced houses on pedestrian wind. (8th August 2020) - Salim, Sheikh Ahmad Zaki Shaikh; Razali, Mohamad Nor Hafidz Arif; Ikegaya, Naoki; Mohammad, Ahmad Faiz; Ali, Mohamed Sukri Mat
Abstract : The present study used large eddy simulations (LES) to examine the pedestrian wind velocity distribution for several cases of terraced houses with extensions. Two simulation cases of idealized terraced houses were performed with extension elements in square (E-SQ) and staggered (E-ST) arrangements. These extension elements were treated as secondary roughness. A simulation of the terraced houses without extension (NE) was also performed to provide a baseline comparison. The mean velocity distribution from LES showed that the secondary roughness strictly limited the flow penetration in both cases, which reduced the turbulent kinetic energy (TKE) inside the canyon. In comparison, E-ST had a stronger effect on TKE than E-SQ with a maximum difference of 19%. Downwind extension elements severely reduced the wind speed at the street and neighbors' houses by about 40% to 50%. However, upwind extension elements increased the wind speed at neighbors' houses about threefold compared to NE. The weak pedestrian wind speed at upwind houses was improved about twelve times with E-SQ and eight times with E-ST when neighbors extended their houses. This indicates that the secondary roughness significantly influences the wind distribution around buildings. Selecting the extension area is important for providing effective outdoor flow conditions.